2008
DOI: 10.1021/jf800773k
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Pesticides in Nuts by Online Reversed-Phase Liquid Chromatography−Gas Chromatography Using the Through-Oven Transfer Adsorption/Desorption Interface

Abstract: A new method to determine pesticide residues in nuts is presented, in which the pesticides are extracted from samples with a small amount of ethyl acetate and anhydrous sodium sulfate. No additional cleanup or concentration steps are necessary. The extract is directly injected into the high-pressure liquid chromatograph, where preseparation of the pesticide residues from other components coextracted from the nuts is carried out using methanol/water as the eluent. The selected liquid chromatography fraction con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Concerning the analysis of pesticide residues in peanut, there are only few works in the published (Li et al 2007a;Cortes et al 2008;Wang et al 2009). In most cases, studies have been carried out only for insecticides or more particular group of insecticides like organophosphorous (OPs) (Li et al 2007b, Su et al 2011, whereas methods are mostly available to determine pesticide residues in peanut oil and only few studies reported in raw peanut.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the analysis of pesticide residues in peanut, there are only few works in the published (Li et al 2007a;Cortes et al 2008;Wang et al 2009). In most cases, studies have been carried out only for insecticides or more particular group of insecticides like organophosphorous (OPs) (Li et al 2007b, Su et al 2011, whereas methods are mostly available to determine pesticide residues in peanut oil and only few studies reported in raw peanut.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the cultivation of nut, pesticides are widely used either solely or in various combinations. And some of them are hydrophobic and can be absorbed in the lipidic matrix of the nuts (fat content 50–70%) . These residues would cause hazardous effects to both humans and environment, and has become of increased concern world wide.…”
Section: Introductionmentioning
confidence: 99%
“…Cortes et al. utilized a LC–GC platform to determine pesticides in nuts after extraction with a small amount of AcOEt and anhydrous sodium sulfate . Haroldo et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TOTAD interface has been used for the on-line LC-GC analysis of many different analytes in complex matrices such as food [14,15] or environmental samples [16,17]. Toledano et al [13] designed an automatic fraction collector which permits the different fraction eluted in LC to be stored automatically and sent individually to the GC by means of the TOTAD interface.…”
Section: Introductionmentioning
confidence: 99%